Environmentally-friendly production of pulp and paper - Bajpai, P. (Pratima) (Wiley, 2010)
Implementing Cleaner Production in the pulp and paper industry. The large--and still growing--pulp and paper industry is a capital- and resource-intensive industry that contributes to many environmental problems, including global warming, human toxicity, ecotoxicity, photochemical oxidation, acidification, nutrification, and solid wastes. This important reference for professionals in the pulp and paper industry details how to improve manufacturing processes that not only cut down on the emission of pollutants but also increase productivity and decrease costs. Environmentally Friendly Production.